The Influence of Information and Communication Technology on Entrepreneurial Literacy through MSME Performance - Hasyim, Sitti Hajerah; Nurjannah, Nurjannah; Arisah, Nur (Cita konsultindo, 2024)
This research aims to understand how information and communication technology has an impact on entrepreneurial literacy through the performance of MSMEs. MSME entrepreneurs are the target population in this study, which also includes a large sample size of 50 respondents. Proportional stratified random sampling is the distribution of questionnaires used. The method used in this study is path analysis. The results of this study are that information and communication technology has a significant effect on entrepreneurship & information technology and technology and entrepreneurship have a significant effect on the performance of MSMEs. Meanwhile, simultaneously it shows that the variables of information technology, technology, and entrepreneurial orientation together have a significant effect on the performance of MSMEs. The implication in this study is that the Disperindagkop provides training to MSMEs on the benefits of using information and communication technology more intensively and the training is carried out on target and applicatively as needed. For MSME entrepreneurs, they must be able to take advantage of information and communication technology facilities to increase their business and be willing to take part in training on information and communication technology held by the Disperindagkop and other parties.